Foot Reflexology Massage for Hypertension in the Elderly: A Case Study - Nursafitri, Riska; Puspita, Tantri; Suliyawati, Eti (Nursing Case Insight Journal, 2026)
Non-communicable diseases (NCDs) have become a public health problem. One of the diseases included in NCDs is hypertension. Hypertension is a condition in which systolic blood pressure increases to 140 mmHg or more and diastolic blood pressure increases to 90 mmHg or more based on two or more measurements. The global prevalence of hypertension is more than 30% of the world's total population. In Indonesia, hypertension also increased in 2018, namely from 34.11% of the total population. Based on the incidence rate, age is one of the causes of hypertension. With increasing age, organ function decreases, affecting sympathetic nerve function, increasing renin secretion, and increasing angiotensin II and aldosterone production. This case study aims to determine the effectiveness of foot reflexology massage therapy in elderly people with hypertension. The method used is a descriptive case study by conducting anamnesis, observation, physical examination, and medical records. The tool used was a sphygmomanometer. The study was conducted on Mrs. T, a 64-year-old female with hypertension. Providing regular foot reflexology massage to hypertensive patients affects the contraction of capillary walls so that vasodilation or widening of the capillary blood vessels and lymph vessels occurs, which results in a decrease in blood pressure from 175/85 mmHg to 150/85 mmHg. The flow of oxygen in the blood increases, the disposal of metabolic waste becomes smoother, thus stimulating the endorphin hormone which functions to provide a sense of comfort and reduce pain in Mrs. T. Regular foot reflexology massage techniques are effective in lowering blood pressure in the elderly with hypertension.